Leading Equine-Assisted Mental Health Groups: An Exploratory Survey of Practitioner Characteristics, Practices, and Professional Development. Issue 2 (3rd April 2018) - Schroeder, Katy; Stroud, Daniel; Erdman, Phyllis
ABSTRACT: This exploratory survey was an investigation of practitioner and practice characteristics of clinicians (N = 24) involved in the provision of equine-assisted mental health (EAMH) groups. We focused on practitioner education, credentialing, clinical experience, approach, and perceived self-efficacy, as well as specific group characteristics concerning type, duration, and clinical populations served. Results, limitations, and future directions are provided, with an overall aim of contributing to the development and progression of this increasingly used group approach.